Recombinant vp1 and vp2 of Infectious Pancreatic Necrosis Virus Trigger Lymphoid Cell Changes and Induced Cytokine Transcriptional Expression in Rainbow Trout Head Kidney - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Ruiz-Higgs, D; Barraza-Rojas, F (Academic Press, 2019)
Sin Resumen Disponible